Long-term improvement by ozone treatment in chronic pain secondary to chemotherapy-induced peripheral neuropathy: A preliminary report - Clavo, Bernardino; Rodríguez-Abreu, Delvys; Galván, Saray; Federico, Mario; Martínez-Sánchez, Gregorio; Ramallo-Fariña, Yolanda; Antonelli, Carla; Benítez, Gretel; Rey-Baltar, Dolores; Jorge, Ignacio J; Rodríguez-Esparragón, Francisco; Serrano-Aguilar, Pedro (Frontiers in Physiology, 2022)
Background: Pain secondary to chemotherapy-induced peripheral neuropathy (CIPN) can limit the administration of chemotherapy, cancer-treatment outcomes, and quality of life of patients. Oxidative stress and inflammation are some of the key mechanisms involved in CIPN. Successful treatments for CIPN are limited. This report shows our preliminary experience using ozone therapy as a modulator of oxidative stress in chronic pain secondary to CIPN. Methods: Ozone therapy, by rectal insufflation, was administered in patients suffering from pain secondary to grade II or III CIPN. Results: All patients, except one, showed clinically relevant pain improvement. Median pain score according to the visual analog scale was 7 (range: 5-8) before O3T, 4 (range: 2-6) at the end of O3T (p = 0.004), 5.5 (range: 1.8-6.3) three months after the end of O3T (p = 0.008), and 6 (range: 2.6-6.6) six months after the end of O3T (p = 0.008).The toxicity grade, according to the Common Terminology Criteria for Adverse Events (CTCAE v.5.0), improved in half of patients. Conclusions: This report shows that most patients obtained clinically relevant and long-lasting improvement in chronic pain secondary to CIPN after treatment with ozone therapy. These observed effects merit further research and support our ongoing randomized clinical trial (NCT04299893).